Targeting Prefrontal Cortical Systems for Drug Development: Potential Therapies for Cognitive Disorders - Arnsten, Amy F.T. (Annu Rev Pharmacol Toxicol, 2016)
Medications to treat cognitive disorders are increasingly needed, yet researchers have had few successes in this challenging arena. Cognitive abilities in primates arise from highly evolved N-methyl-d-aspartate (NMDA) receptor circuits in layer III of the dorsolateral prefrontal cortex. These circuits have unique modulatory needs that can differ from the layer V neurons that predominate in rodents, but they offer multiple therapeutic targets. Cognitive improvement often requires low doses that enhance the pattern of information held in working memory, whereas higher doses can produce nonspecific changes that obscure information. Identifying appropriate doses for clinical trials may be helped by assessments in monkeys and by flexible, individualized dose designs. The use of guanfacine (Intuniv) for prefrontal cortical disorders was based on research in monkeys, supporting this approach. Coupling our knowledge of higher primate circuits with the powerful methods now available in drug design will help create effective treatments for cognitive disorders.